Paramilitarism and music in Colombia An analysis of the corridos paracos (2019)
Colombia has experienced violence at the hands of both guerrillas and paramilitaries fighting to control territories, drug trafficking, and gain political influence. Though in recent years armed activities by both groups has subsided, their conflicting ideologies are visible in several contexts in today's polarized Colombia. We tend to think about conflict in terms of bullets and people in military uniforms, but discourses of conflict are also evident in popular culture, such as music. In this paper, we analyse 19 corridos paracos, videos produced by sympathisers of Right-wing guerrilla groups, to demonstrate how this is done. Here, we find songs present a messianic portrayal of the paramilitary along with sexist ideas as the representation of manliness. Moreover, there is an almost total absence of peaceful actions in the lyrics, and an exaltation of brutality and terrorism. In a political context which cries out for reconciliation, these do little to this end. © John Benjamins Publishing Company.